Barriers to implementing nursing evidence-based practice at the Palestinian Medical Complex: A cross-sectional study - Hamdallah H. Khaled (Journal of Family Medicine and Primary Care)
Background: The use of nursing evidence-based practice (EBP) has grown more and more important for healthcare professionals globally in their goal of delivering high-quality patient care. Objective: The aim of this study is to assess barriers to implementing EBP among Palestinian nurses at the Palestinian Medical Complex (PMC). Methods: The study was carried out at the PMC over the course of a month and employed a cross-sectional descriptive approach. Data were gathered from 100 nurses who satisfied the inclusion criteria by using convenient sampling. Barriers to the application of EBP were measured by the BARRIER Scale. Results: Participants identified key barriers such as inadequate time (62%, M ± SD: 3.34 ± 1.066) and lack of assistance (30%, M ± SD: 3.15 ± 1.029). Concerns included literature dispersion (45%, M ± SD: 3.23 ± 0.973), inadequate facilities (53%, M ± SD: 3.70 ± 1.010), and methodological issues (52%, M ± SD: 3.16 ± 1.012). In addition, 57% felt that research is published too slowly (M ± SD: 3.39 ± 0.898), 33% noted unjustified conclusions (M ± SD: 3.01 ± 0.882), and 35% highlighted a lack of replication (M ± SD: 3.07 ± 0.879). Conclusion: This study found that head nurses and men perceived more significant barriers to research quality, while individuals with baccalaureate degrees reported fewer barriers. There was an association between perceived barriers and age and work experience, indicating age as a positive predictor of barriers related to research quality.